Sensitivity and Specificity of the SelfAdministered HPV Testing in Detecting Precancerous Conditions of the Cervix and Cervical Cancer: sensitivitas dan Spesifisitas Pemeriksaan Mandiri dalam Mendeteksi Lesi Prakanker dan Kanker Serviks - Erny M Nyngsi; Syahrul Rauf; Eddy Moeljono (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the sensitivity and specificity of selfadministered Human Papilloma virus (HPV) test in detecting pre-cancerous lesions and high degree cervical cancer. Methods: A case control study design was used in this study. This study was conducted at Dr. Wahidin Sudirohusodo Hospital and its affiliate hospitals during the period of October 2014 to May 2015. Measurement data using HPV self test grant from the Dutch School Netherlands, Evalyn Brush. Collecting data used questionnaires before and after doing HPV self test. Laboratory tests are carried out in Kalbe Genomic using HPV Genotyping capable detect 35 types of the HPV virus. Results: A total of 101 subjects were involved in this study. The subjects were divided into two groups, the case and the controls (n = 50/51). Level of sensitivity and specificity were obtained for HPV self test (56% vs 98%). The level of acceptance of new tests by 62.37% (63 out of 101 respondents) of them admitted that the new test is simple / easy enough to do. The acuracy rate of diagnostic test of this examination is 79%. Conclusion: Self-administered HPV test could be used as an alternative or primary screening for cervical cancer. [Indones J Obstet Gynecol 2017; 5-3: 173-179] Keywords: HPV, self, specificity, the sensitivity